Immune responses in a mouse model of vitiligo with spontaneous epidermal de‐ and repigmentation. (21st July 2014) - Eby, Jonathan M.; Kang, Hee‐Kap; Klarquist, Jared; Chatterjee, Shilpak; Mosenson, Jeffrey A.; Nishimura, Michael I.; Garrett‐Mayer, Elizabeth; Longley, B. Jack; Engelhard, Victor H.; Mehrotra, Shikhar; Le Poole, I. Caroline
Summary To generate a mouse model of spontaneous epidermal depigmentation, parental h3TA2 mice, expressing both a human‐derived, tyrosinase‐reactive T‐cell receptor on T cells and the matching HLA‐A2 transgene, were crossed to keratin 14‐promoter driven, stem cell factor transgenic (K14‐SCF) mice with intra‐epidermal melanocytes. In resulting Vitesse mice, spontaneous skin depigmentation precedes symmetrical and sharply demarcated patches of graying hair. Whereas the SCF transgene alone dictates a greater retinoic acid receptor‐related orphan receptor gamma (RORγt)+ T‐cell compartment, these cells displayed markedly increased IL‐17 expression within Vitesse mice. Similar to patient skin, regulatory T cells were less abundant compared with K14‐SCF mice, with the exception of gradually appearing patches of repigmenting skin. The subtle repigmentation observed likely reflects resilient melanocytes that coexist with skin‐infiltrating, melanocyte‐reactive T cells. Similar repigmenting lesions were found in a different TCR transgenic model of vitiligo developed on an SCF transgenic background, supporting a role for SCF in repigmentation.